Transcription organizes euchromatin via microphase separation - Hilbert, Lennart; Sato, Yuko; Kuznetsova, Ksenia; Bianucci, Tommaso; Kimura, Hiroshi; Jülicher, Frank; Honigmann, Alf; Zaburdaev, Vasily; Vastenhouw, Nadine L. (Nature Communications, 2021)
In eukaryotes, DNA is packed inside the cell nucleus in the form of chromatin, which consists of DNA, proteins such as histones, and RNA. Euchromatin, which is permissive for transcription, is spatially organized into transcriptionally inactive domains interspersed with pockets of transcriptional activity. While transcription and RNA have been implicated in euchromatin organization, it remains unclear how their interplay forms and maintains transcription pockets. Here we combine theory and experiment to analyze the dynamics of euchromatin organization as pluripotent zebrafish cells exit mitosis and begin transcription. We show that accumulation of RNA induces formation of transcription pockets which displace transcriptionally inactive chromatin. We propose that the accumulating RNA recruits RNA-binding proteins that together tend to separate from transcriptionally inactive euchromatin. Full phase separation is prevented because RNA remains tethered to transcribed euchromatin through RNA polymerases. Instead, smaller scale microphases emerge that do not grow further and form the typical pattern of euchromatin organization.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Biophysics; Cell biology